Promoting Entrepreneurial Development through Millet Processing in Raichur District, Karnataka, India - Mouneshwari R. Kammar; Vanishree S.; Udaykumar Nidoni (Research Advances and Challenges in Agricultural Sciences Vol. 4, 2024)
Millets are small grain crops and are also known as mighty millets because of their nutrients. Processing of millets provides an opportunity for income generation and also ensures food security to the family as well as to the animals through fodder. This paper explains the efforts made by KVK Raichur, University of Agricultural Sciences, Raichur in promoting entrepreneurship development through primary and secondary processing, and value addition of millets and their role in income enhancement of farmers. The target population for this study comprised 50 beneficiaries from SHGs under the jurisdiction of UAS, Raichur, Karnataka, India. The major activities undertaken for the research population were the promotion of high yielding variety of foxtail millet (HMT-100-1 and Variety-SIA-2644), the development of value chains of nutritious millets, training women members of SHGs on value addition, establishing marketing linkages for the processed produce through demonstrations and trainings. It was found that the farmers whose lands do not possess an irrigation facility and have very poor fertility status had undertaken cultivation of millets and the KVK had linked them up to the processing unit of the Department of Processing and Food Engineering department for primary and secondary processing through demonstrations and training. It was found that farmers and SHGs gained technical know-how and ways to become entrepreneurs. Small millet crops are important for the food security and income of poor farmers in certain agroclimatic regions but it has not received adequate attention from the policymakers for the purpose of investment in their research and development. Poverty incidence can thus become reduced with increased investment in people, improving their quality and enhancing their employment prospects.